Can US Economic Variables Predict Chinese Stock Market? - GOH, Jeremy (Institutional Knowledge at Singapore Management University, 2012)
In the last few decades, we observed a significant increase in global economic activities and these activities may have an impact on both China's economy and stock market. Given the potential impact, we empirically examine whether US economic variables are leading indicators of the Chinese stock market. Prior to China joining the World Trade Organization (WTO) in the end of 2001, we find no statistical relationship between US economic variables and the Chinese stock market returns. However, we find US economic variables have statistically significant predictive power for periods after China's admission into the WTO. In addition, we show that the combination of US and China economic variables is more superior in terms of forecasting ability than either single country economic variables. These findings are of economic importance from an investment perspective.